2012
DOI: 10.1159/000341218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Displays and Room Illuminance on Caries Diagnostic Accuracy in Digital Dental Radiographs

Abstract: In clinical practice, digital radiographs taken for caries diagnostics are viewed on varying types of displays and usually in relatively high ambient lighting (room illuminance) conditions. Our purpose was to assess the effect of room illuminance and varying display types on caries diagnostic accuracy in digital dental radiographs. Previous studies have shown that the diagnostic accuracy of caries detection is significantly better in reduced lighting conditions. Our hypothesis was that higher display luminance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Hellén-Halme et al 15 concluded that it was easier to detect dentinal caries in dim conditions than in bright conditions, whereas with enamel caries, there were no differences between the lighting when the display was adjusted for optimal brightness and contrast. Pakkala et al 19 also concluded that different displays and room illuminance levels did not affect the overall accuracy of intraoral radiographs in enamel caries detection. In the present study, DICOM calibration significantly improved enamel caries interpretation as compared with uncalibrated display in bright lighting.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hellén-Halme et al 15 concluded that it was easier to detect dentinal caries in dim conditions than in bright conditions, whereas with enamel caries, there were no differences between the lighting when the display was adjusted for optimal brightness and contrast. Pakkala et al 19 also concluded that different displays and room illuminance levels did not affect the overall accuracy of intraoral radiographs in enamel caries detection. In the present study, DICOM calibration significantly improved enamel caries interpretation as compared with uncalibrated display in bright lighting.…”
Section: Discussionmentioning
confidence: 97%
“…14 Several in vitro studies have investigated the effect of varying displays on detecting interproximal caries in digital intraoral radiographs. [14][15][16][17][18][19][20][21] In these studies, some technical parameters were investigated, i.e. the effect of DICOM calibration, ambient light, luminance and monitor contrast and brightness settings.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Hellén-Halme et al 4,13 concluded that there was no evidence that room illuminance affected the ability to detect carious lesions in digital intraoral radiographs as long as the display was calibrated in accordance with the surrounding light level. Pakkala et al 14 compared an off-the-self colour display, a DICOM-calibrated colour liquid crystal display and a DICOM-calibrated greyscale liquid crystal display in varying room illuminance. They showed that different displays and room illuminance levels did not affect the overall detection of caries lesions in intraoral images.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating the effect of different displays on caries diagnostic accuracy in intraoral radiographs have been published. 2,4,5,[13][14][15][16][17] However, only one study has investigated the use of tablets 3 and two studies the use of medical displays as devices to view panoramic images. 3,12 It has not been investigated how DICOM calibration in consumer grade displays affect the diagnostic accuracy of observing anatomical structures and pathology in panoramic radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…The correlating numbers in the present study were slightly higher but the actual figures cannot be compared since the observers were not the same. Other studies 5,10,11 have previously concluded that diagnostic accuracy for detection of very faint objects, such as small carious lesions, is highly dependent on standard display monitor calibration and control of ambient lighting. In this study, it was shown that it is in fact possible to evaluate radiographic images for carious lesions when the ambient light is high.…”
Section: Discussionmentioning
confidence: 99%